Does anyone need help? Age and gender effects on children's ability to recognize need-of-help - Stolarova, Margarita; Brielmann, Aenne A. (Frontiers in Psychology, 2014)
The exploratory study presented here examines children’s ability to recognize another person’s need-of-help. This social perception process necessarily precedes the decision to actively help others. Fifty-eight children aged between five and 13 completed three experimental paradigms. They were asked to look at black-and-white drawings and to indicate which ones showed somebody in need of help. A control task requiring children to differentiate between pictures of humans and birds measured general categorization abilities. This experimental design enabled us to consider confounding effects of children’s developmental status and motivation and to distinguish them from specific need-of-help recognition abilities. As gender and age have been shown to influence social perception as well as helping behavior, we explored whether these factors also have an impact on need-of-help recognition. Children’s response accuracies and response times were analyzed. We observed clearly higher accuracy rates for younger girls compared to younger boys specifically in the need-of-help recognition tasks. For boys, an age-related performance improvement was found. Younger girls performed at a similarly high level as older girls and boys. No gender differences were observed for children aged over nine. This report provides first evidence that the developmental trajectory of children’s ability to recognize another person’s need-of-help differs for girls and boys.